The friction and wear behaviors of self-lubricating composites with two types of warp-knitted fabric structures. Issue 5 (June 2022) - Yu, Mingming; Wang, Sha; Ren, Fang; Wu, Ying; Ren, Musu; Li, Yingjun; Ma, Pibo
Replacing the traditional self-lubricating fabric composites with new type of wear-resistant composite reinforced by warp-knitted fabrics PTFE-Nomex and PTFE-Nomex/Nomex (self-lubricating fiber: PTFE, reinforcing fiber: Nomex), in which the hybrid graphite/graphene particle modified phenolic is used as the adhesive resin. The influence of the fabric structure on the friction and wear properties of self-lubricating fabric composites was evaluated by the ball-on-disk and bearing friction tests. And the wear mechanism of the composites was investigated through scanning electron microscopy (SEM) and mechanical tests. The ball-on-disk friction test shows that the friction and wear properties of two kinds of composites with different structures are different with the increase of friction distance. In addition, the self-lubricating warp-knitted composite materials were prepared as self-lubricating joint bearing liners to evaluate the bearing application. It is proposed that the wear resistance of the two kinds of warp-knitted composites is poor, and the single layer is slightly better. It is related to the friction mode, mechanical and bonding properties of the bearing liners.